C-reactive protein predicts response to infliximab in patients with chronic sarcoidosis - Sweiss, N.J.; Barnathan, E.S.; Lo, K. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Background: This study assessed the value of C-reactive protein as a predictor of disease severity and response to infliximab therapy in patients with chronic pulmonary sarcoidosis. Design: Sera were collected through week 52 from 138 patients with chronic pulmonary sarcoidosis who received placebo or infliximab in a randomized, double-blind, placebo-controlled study.We evaluated the response to therapy by baseline CRP using a dichotomous cutpoint (0.8 mg/dL) for the change from baseline in percent-predicted forced vital capacity (FVC), Saint George’s Respiratory Questionnaire (SGRQ), 6-minute walk distance (6MWD), Borg’s CR10 dyspnea score, and Physician Organ Assessment (POA). Results: CRP was elevated in 36% of patients at baseline, and was significantly reduced by infliximab by week 2. Among patients with elevated baseline CRP, infliximab-treated patients improved significantly compared with placebo-treated patients in percent-predicted FVC (+2.5 versus –2.6%), 6MWD (+8.0 versus –34.1), Borg’s CR10 dyspnea score (pre-6MWD –0.8 versus +0.9, post-6MWD –1.1 versus +0.8), and POA (–3.1 versus –0.3). Patients with lower CRP levels at baseline did not show significant differences between the placebo and infliximab groups in most endpoints evaluated. Conclusions: In chronic sarcoidosis patients, elevated CRP appears to identify a subset with more severe disease who may respond better to treatment with infliximab.